Predicting the chaos and solution bounds in a complex dynamical system - Chien, Fengsheng; İnç, Mustafa; Yosefzade, Hamidreza; Nik, Hassan Saberi (Pergamon-Elsevier Science Ltd, 2021)
The competitive modes for a nonlinear chaotic complex system are studied in this paper. In hyperchaotic, chaotic, and periodic cases, we examined competitive modes that are a tool for detecting chaos in a system. Also, using an analytical method and Lagrange optimization, we were able to calculate the ultimate bound of the nonlinear chaotic complex systems. We have presented is simpler and more accurate than other methods that implicitly calculate the ultimate bound. The estimation of the explicit ultimate bound can be used to study chaos control and chaos synchronization. Numerical simulations illustrate the analytical results. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Nonlinear chaotic complex system; Explicit ultimate bound; Lagrange multiplier method; Optimization